Factors affecting financial fraud awareness among university students - Liew, Yoon Ler (2024)
This purpose of this research is to evaluates the factors that affecting the financial fraud awareness among university students. In this research, the independent variables which had been identified by the researcher are anti-fraud education, attitudes towards fraud and defensiveness against fraud while the dependent variable is the financial fraud awareness among university students. The 2 underlying theories that had been applied in this study are the Theory of Planned Behaviour (TPB) and the Protection Motivation Theory (PMT). Furthermore, a conceptual framework for the variables had been developed in this research as well. This study uses primary data to collect all the 250 respondents by utilizing the survey questionnaire. A pilot test had been conducted by the researcher as well before the commencement of the main and actual survey. The researcher also uses the descriptive analysis, reliability test and the inferential analysis (Multiple Regression Analysis & Pearson Correlation Coefficient Analysis) as the data analysis tools to conduct the study. Finally, the results successfully showed and proved that all of the identified 3 factors (Anti-Fraud Education, Attitudes Towards Fraud & Defensiveness Against Fraud) will have a significant positive relationship with the financial fraud awareness among university students. The main contribution in this research is this study could help and assist in providing an excellent insight and better understanding for the university students, organizations, policy makers as well as the Malaysians on the financial fraud in order to boost their awareness and knowledge on it. The implications, limitations and certain recommendations of this study had also been reported and stated by the researcher in this research as well